A pilot study of seasonal and interannual patterns in the distribution of chlorophyll α and temperature over three areas of the southwest Indian Ocean: northeast Madagascar, southeast Madagascar and the Mascarene Islands - Komul, Bhavnah (Department of Oceanography, 2017)
Remotely sensed weekly MODIS data of chlorophyll α (Chl-α) concentration, sea surface temperature (SST) and satellite altimetry data of Absolute Dynamic Topography (ADT) and geostrophic velocities are used to examine the seasonal and interannual patterns in the Chl-α concentration and SST over three pilot study areas of the southwest Indian Ocean, namely Northeast Madagascar, Southeast Madagascar and Mascarene Islands. The weekly and monthly climatology and the weekly means of each variables are assessed using image displays and time series from 2003 to 2014. It is found that there is a seasonal cycle of phytoplankton blooms occurring twice a year across northeast and southeast Madagascar. The two blooms occur during the summer monsoon and during the winter monsoon, respectively. Unlike these two areas, the Mascarene Islands area has only one bloom during the summer monsoon. There is a negative correlation between SST and Chl-α concentration across all three areas; when SST is high, Chl-α concentration is low and vice versa. Also, the current patterns showed that the two Madagascar study areas, are more physically dynamic than the Mascarene Islands region. Unlike the Masacarene region, the Madagascar regions are more affected by the forcing of the South Equatorial Current that splits into the Southeast Madagascar Current and Northeast Madagascar Current, thus causing displacement of surface water. New outcomes of this study are that the north Indian Ocean (north of 100S) is not the only area that is affected by the summer and winter monsoons but the areas south of 100S may also be indirectly affected by the monsoons. Across Northeast Madgascar region, the summer monsoon bloom is well spread over the area while the winter monsoon bloom is mostly coastal. Across the Southest Madagascar region, the summer monsoon bloom spreads from east to west while, the winter monsoon bloom spreads from west to east. The Mascarene region is less productive with higher sea surface height and weaker eddies compared to the other areas and the mixed layer depth is greater across the Mascarene region, thus less nutrients are injected to the euphotic zone and the weaker eddies result in less mixing and consequently in weak Chl-α production. This study should improve our understanding of the seasonal and interannual variability of the SST and Chl-α and the dynamics of the ADT and geostrophic velocities in these regions for improved management of fishery resources using an ecosystem approach to fisheries.